A new species of Cnemaspis Strauch 1887 (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia with an updated checklist of the herpetofauna of Tuba Island - Quah, Evan S. H.; Wood, Perry L. Jr.; Anuar, M.s. Shahrul; Muin, Mohd Abdul (Zootaxa, 2020)
A new, diminutive species of Rock Gecko Cnemaspis tubaensis sp. nov. of the C. kumpoli group, is described from Tuba Island, Langkawi Archipelago, Kedah, Peninsular Malaysia and is differentiated from all other species in the kumpoli group by having a unique combination of morphological and color pattern characteristics, including a maximum SVL of 37.0 mm; 10 or 11 supralabials; eight or nine infralabials; 15–18 semi-linearly arranged paravertebral tubercles; lateral caudal furrow present; lateral caudal tubercles on the anterior portion of the tail; caudal tubercles not encircling tail; five or six precloacal pores; 28 or 29 subdigital lamellae on the fourth toe; smooth ventrals; smooth subcaudals with an enlarged median row of scales; subcaudal region light-grey and speckled with yellow; absence of light-colored ocelli on the shoulder; no yellow postscapular band; dorsum light-brown with sage-green blotches and black spots; flanks with scattered yellow spots; absence of black gular markings in both sexes; and 13.0–22.0% uncorrected pairwise sequence divergences in the NADH dehydrogenase subunit 2 gene (ND2). Cnemaspis tubaensis sp. nov. is the fourth species of Cnemaspis to be described from the Langkawi Archipelago and underscores the underestimated biodiversity of the islands which is in need of more thorough herpetological inventories.